Power system measurements based on fuzzy linear regression algorithm for power system protection - Soliman, S.A.; Rahman, M.H.A.; El-Hawary, M.E. (Conference proceedings - Canadian Conference on Electrical and Computer Engineering, 1996)
This paper presents a new technique for power system voltage measurements based on fuzzy linear regression. The voltage signal is assumed to have a linear relation with the voltage magnitude and the phase angle. The coefficients of this linear relation are considered as fuzzy numbers with given middle and spread values. The spread defines the fuzziness of the function. The proposed technique uses digitized samples of the voltage signal obtained at the relay location. The problem is formulated as a linear optimization problem, where the objective is to minimize the spread of the fuzzy output for the whole data set, which is a linear function of the spread, subject to satisfying inequality constraints. A linear programming algorithm is used to solve the associated linear optimization problem. The proposed technique is tested using nonfuzzy as well as fuzzy data.